Complex Governance Does Increase Both the Real and Perceived Registration Burden: The Case of the Netherlands; Comment on "Perceived Burden Due to Registrations for Quality Monitoring and Improvement in Hospitals: A Mixed Methods Study" - Patrick PT Jeurissen; Niek Klazinga; Luc Hagenaars (Kerman University of Medical Sciences, 2022)
The burden of registrations for professionals should be more firmly on the policy agenda. In a rigorous study, Marieke Zegers and colleagues make a compelling argument why that should be the case. In Dutch hospitals, the average professional spends 52.3 minutes a day on quality registries and monitoring instruments. Many more administrative duties exist. These represent substantial resources and ultimately could become a drag on the intrinsic motivation of the care professions. We agree with Zegers et al that we are in need for more operational efficiency. However, the issue at hand is very complex and also intensely connected to the entire healthcare system and its different levels. More operational efficiency alone will not solve this problem. We are also in need for better governance of data-issues at the macro-system level.